Управління маркетинговими ризиками: теоретичний та прикладний аспект - Солнцев, С. О.; Овчиннікова, А. В. (Видавництво Львівської політехніки, 2012)
Розглянуто сутність управління ризиками та підходи авторів до виділення етапів управління ризиками. Запропоновано виділити процес оцінювання ризиків у окремий етап управління ризиками. Розглянуто особливості управління маркетинговими ризиками. Проаналізовано основні стратегії управління ризиками та інструменти управління ризиком у межах кожної зі стратегії, визначено переваги та недоліки їх застосування в Україні. The essence of risk management and approaches of the authors to the definition of stages of risk management have been analyzed. The academicians have different standpoints on separation of the risk management stages. The separation of the process of risk evaluation into separate risk management stage has been proposed. The particularities of the marketing risks management have been analyzed. The main risk management strategies and risk management techniques within each strategy have been examined. The advantages and disadvantages of risk management techniques have been defined. It has been identified that a considerable part of risk management techniques cannot be used in Ukraine because of the missing relevant standard acts. Also, the efficiency of some risk management techniques is lower than in the European countries or USA. Under the conditions of permanent market transformation processes, the companies which provide the risk management services are going to develop.
Theoretical and applied aspects of marketing risk management
Keywords: ризик; маркетинговий ризик; управління ризиками; оцінювання ризиків; інструменти управління ризиками; risk; marketing risk; risk management; risk evaluation; risk management techniques